Are banks less likely to issue equity when they are less capitalized? - Valeriya Dinger; Francesco Vallascas (Osnabrück University, Institute of Empirical Economic Research, 2014)
Debt overhang and moral hazard related to risk-shifting opportunities predict that low capitalized banks have a lower likelihood to issue equity. In contrast to this view, for an international sample of bank Seasoned Equity Offerings (SEOs), we show that the likelihood of issuing an SEO is generally higher in low capitalized banks. We provide a series of tests exploring the variation of capital regulation, systemic conditions and market discipline to understand the driving forces behind this result. We find that market mechanisms rather than capital regulation are the primary, key driver of the decision to issue by low capitalized banks.
Keywords: G21; G28; G32; 330; SEOs; Banking Regulation; Banking Crises; Counter-cyclical capital regulation